Design and Implementation of Remote-Controlled Lawn Mower Using Dual-Tone Multi-Frequency Technology - D. K. Owusu; P. K. Otchere; W. Opare (International Journal of Electrical Engineering and Applied Sciences)
One of the most important machines that assist with retaining the physical shapes and beauty of lawns is lawn mower. There are ranges of styles and shapes for commercial use of heavy-duty mowers to residential use of push mowers. Lawn mower can operate on solar power, electricity or diesel. Some lawn mowers have the capabilities to gather the cut grasses into bags and spread the grasses on the surfaces of the soil to help reduce loss of moisture in the soil. Lawn mowing requires the operator to move to the various locations that the weeding would take place. This causes fatigue to the operator since the operator would have to be standing and moving in the sun for a long time and also could be hit by a stone during the cutting of the weeds. This could lead to injuries to the operator and staying in the sun for long can likewise cause migraine. Furthermore, the exposure to noise from the mower and dust may also be harmful to the health of the operator. To overcome these challenges associated with lawn mowers, their operation can be automated. This paper aims to design and construct a prototype of a remote-controlled lawn mower using dual-tone multi-frequency technology to control the directions of a lawn mower. This research was designed using Arduino Uno, which is based on the ATmega328P microcontroller, 6 VDC geared stepper motor, a 700- HB relay that serves as a motor driver, a sim8001 DTMF module integrated circuit (IC) and a mobile phone